Cuatro compuestos nuevos del extracto no polar de la planta Amyris brenesii (Rutaceae) de Costa Rica - Chavarría, Max; Castro, Víctor; Poveda, Luis; Murillo, Renato (Revista de Biología Tropical, 2008)
Fractionation of a non polar extract of the aerial parts of Amyris brenesii collected in Río Cuarto, Grecia, Costa Ricahas resulted in the isolation of four new compounds, 6-hidroxy-6-O-(3-hidroxymethyl-3-methylalyl)-angelicin1, 6-(N-acetyl-2-etanamin)-2,2-dimethyl-2H-cromen 2, the lignan 2,5-dehidrohinokinin 3 and N-acetyl-O-(geranyl)-tiramine 4. In addition, we isolated six previously known compounds: the lignans hinokinin 5 and Justicidin E 6, the coumarins scopoletin 7 and marmesin 8, 24-moretenoic acid 9, and the nitrogen compound O-(3,3-dimethylalyl)-halfordinol 10. All the separations were done with chromatographic techniques and the structures were elucidated by using 1D and 2D NMR techniques.